Regulation of Intestinal Immune Response by Selective Removal of the Anterior, Posterior, or Entire Pituitary Gland in Trichinella spiralis Infected Golden Hamsters - Bassaganya Riera, Josep; Hernández Cervantes, Rosalía; Quintanar Stephano, Andrés; Moreno Méndoza, Norma; López Griego, Lorena; López Salazar, Valeria; Hernández Bello, Romel; Carrero, Julio César; Morales Montor, Jorge (2013)
The influence of anterior pituitary hormones on the gastrointestinal tract of humans and animals has been previously reported. Hypophysectomy (HYPOX) in the rat causes atrophy of the intestinal mucosa, and reduction of gastric secretion and intestinal absorption, as well as increased susceptibility to bacterial and viral infections. However, to our knowledge, no findings have been published concerning the immune response following HYPOX during worm infection, particularly that which is caused by the nematode Trichinella spiralis. The aim of this work was to analyze the effects of total or partial HYPOX on colonization of T. spiralis in the intestinal lumen, together with duodenal and splenic cytokine expression. Our results indicate that 5 days post infection, only neurointermediate pituitary lobectomy (NIL) reduces the number of intestinally recovered T. spiralis larvae. Using semiquantitative inmunofluorescent laser confocal microscopy, we observed that the mean intensity of all tested Th1 cytokines was markedly diminished, even in the duodenum of infected controls. In contrast, a high level of expression of these cytokines was noted in the NIL infected hamsters. Likewise, a significant decrease in the fluorescence intensity of Th2 cytokines (with the exception of IL-4) was apparent in the duodenum of control and sham infected hamsters, compared to animals with NIL surgeries, which showed an increase in the expression of IL-5 and IL-13. Histology of duodenal mucosa from NIL hamsters showed an exacerbated inflammatory infiltrate located along the lamina propria, which was related to the presence of the parasite. We conclude that hormones from each pituitary lobe affect the gastrointestinal immune responses to T. spiralis through various mechanisms.